Assessment of Type and Severity of Tooth Wear in Geriatric Patients: A Clinical Survey - Meshramkar, Roseline; Lekhaq, K.; Anehosur, Gouri V.; Nadiger, Ramesh K. (Highlights on Medicine and Medical Science Vol. 5, 2021)
There has been an increasing interest in tooth wear in dental literature. Tooth wear is commonly found in every dentition. Problems associated with tooth wear in elderly is increasing. A clinical survey was conducted to assess the type and severity of tooth wear in Geriatric patients. A total of 148 patents were surveyed out of which 128 M 40 F with mean average age of 60-80 yrs. The history was recorded with a with a questionnaire. Depending on the feedback for all these questions were to categorize the patients into one of the following etiological categories. Attrition, Abrasion, erosion, combination of tooth wear and clinical examination was done to asses the type of tooth wear and the extent of tooth wear was assessed using smith and knight index. Out of 148 patients all patients had tooth wear, 129 patients had attrition, 14 patients had abrasion, 5 patients had erosion and 82 patients had combination of tooth wear. 62 patients had Grade I, 38 patients had Grade II, 28 patients had Grade III, 3 Patients had Grade IV. It is very necessary to know the epidemiological survey of tooth wear in geriatric patients among Indian population.